EFFECTS OF INDIGENOUS AND FOREIGN POLLINIZERS ON THE YIELD AND FRUIT CHARACTERISTICS OF DATE PALM CULTIVAR KHALAS - & et al., Munir (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
This research was carried out at Research and Training Station, Date Palm Research Center of Excellence, King Faisal University, Al-Ahsa, Saudi Arabia during 2017 and 2018 to investigate the effects of indigenous and foreign pollinizers on the yield and physicochemical fruit characteristics of date palm cv. Khalas. Pollen grains of different date palm male pollinizers were collected from different geological locations of Saudi Arabia and Egypt. Fifteen twelve-year-old date palm trees were selected for the experiment, for which five spathes for each palm were selected per replication. The experiment was laid out as a Randomized Complete Block Design with three replicates for each treatment. The findings of the present study showed significant differences among pollinizer sources. Female date palms pollinated with indigenous male pollen grains (Al-Ahsa, Saudi Arabia) exhibited superior results regarding fruit set percentage, parthenocarpic fruit percentage, tamar fruit percentage, fruit drop percentage, total number of fruit nodes per bunch, bunch weight, pulp weight, pulp ratio, seed ratio and pulp:seed ratio, fruit fresh weight, fruit dry weight, fruit length, fruit width, fruit volume, seed weight, seed length, seed width, fruit moisture content and total soluble solids. It is can be concluded that although the response to pollination and fertilization of date palm is species dependent, however, the indigenous cultivar Khalas was more responsive to the local male types than the foreign males for better fruit set, higher yield and best fruit quality traits.